Research on advanced technologies and their efficiency in the process of interactions between different transport modes in the terminal - Batarlienė, Nijolė; Jarašūnienė, Aldona (Transport, 2009)
The infrastructure of transport means has to be modernized and organized in such a way that operators could employ effective transportation technologies and processes and that the sustainable development of different transport modes and their proper interoperability with the transport systems of the neighbouring states are achieved. The long‐term development strategy of the Lithuanian transport system notes that the solution to the problems of transport technology is based on improvements in technological supply and the rational use of the informational modeling methodology of the whole transportation process. The interaction between different transport modes in the terminal is a complex and multiplex task. To reach a successful solution for this task, a thorough evaluation and analysis of numerous factors is required and a preliminary research of respective elements is necessary. The application of advanced technologies is essential in the terminal where several road transport modes are involved in the process of interaction. Therefore, an information transmission centre (ITC) is necessary. First published online: 27 Oct 2010